2003
DOI: 10.1021/jp027804g
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Surface Structural Properties of Mn2+-Doped ZnSe Nanoparticles

Abstract: Mn 2+ -doped ZnSe nanoparticles were synthesized from molecular cluster precursors. Four ZnSe nanoparticle samples, one with low Mn 2+ concentration (A), one with an intermediate Mn 2+ concentration (B), one with a high Mn 2+ concentration (C), and one with no Mn 2+ , were prepared and characterized using UV-vis, luminescence, electron spin resonance (ESR), and X-ray absorption fine structure (XAFS) techniques. The sample with no Mn 2+ had a sharp ZnSe band edge emission peak and a quantum yield of ∼2%. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 47 publications
8
105
1
Order By: Relevance
“…Moreover, at least in some of the quantum dots, the Mn-Mn interaction is strong enough to reveal the hyperfine splitting. Signal II may arise due to the location of Mn near the surface 5,11,13 of the ZnSe quantum dot. Signal II is superimposed on signal I, and is originated since Mn 2+ has less of a symmetric environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, at least in some of the quantum dots, the Mn-Mn interaction is strong enough to reveal the hyperfine splitting. Signal II may arise due to the location of Mn near the surface 5,11,13 of the ZnSe quantum dot. Signal II is superimposed on signal I, and is originated since Mn 2+ has less of a symmetric environment.…”
Section: Resultsmentioning
confidence: 99%
“…2 High fluorescence efficiency along with magnetic ordering makes Mn an interesting transition element dopant [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] in the semiconductor nanoparticles. Recently, Mn-doped ZnSe nanoparticles [3][4][5][6][7][8][9][10] received much attention since it has the potential application for luminescent as well as spintronic devices. 1 Moreover, the number of Mn ions incorporated at substitutional sites can also modify the lattice parameters as well as the band gap of semiconducting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PLE result collected by monitoring the Mn 2+ 4 T 2 → 6 A 1 transition also indicate, that energy transfer from the photoexcited Cu 2 O nanocrystals to the Mn 2+ gives rise to the blue emission. 20,39 The UV-visible absorption spectrum of sample HMnCP3 shown in the Fig. 4͑d͒, gives a weak broad peak at 632 nm ͑1.96 eV͒ along with four absorption bands at about 280, 293, 334, and 352 nm.…”
Section: -mentioning
confidence: 99%
“…18,19 The engineering of band gap and influencing physical, chemical, and electronic properties of the semiconductors are possible by the use of the right dopants. Norman et al 20 showed the tuning of the emission energy of Mn doped ZnSe nanoparticles. The band gap tuning of the Mn doped CdS quantum dots were observed by Kim.…”
Section: Introductionmentioning
confidence: 99%